Dilemmas of Immigrant Asylum Claims for Expert Witnesses. Issue 1 (4th February 2022) - Jones, Nathan P.; Campbell, Howard
Abstract: Expert witnesses are key players in immigration asylum proceedings. In many cases, their testimony is the difference between prompt deportation and some form of relief. However, political and economic structures overdetermine the factual and legal dimensions of immigrant asylum claims. The U.S. immigration system from its inception has been heavily politicized and discriminatory. The problem has become even more pronounced since the election of Donald Trump as president. This article examines political, economic, and ethical dilemmas of immigrant asylum claims for expert witnesses. These include issues related to the caliber of judges and lawyers, the geographic location of legal proceedings, challenges of telephonic versus in‐person testimony, moral questions regarding whether to participate in a rigged system, the weight given to expert opinions, unrealistic standards of evidence, obstacles to the presentation of social scientific data, and expert witness burnout.